Energy Consumption Analysis and Efficiency Improvements in the Hospitality Sector: A Case Study of Hotel A in Jakarta Tanah Abang - Erfiana Wahyuningsih; Difano Galiano S (Dinasti Research, 2024)
The hospitality industry is known for its high energy use. The operation of many 24-hour facilities raises energy demand. The Minister of Culture and Tourism's Decree Number KM.03/HK.001/MKP.02 requires that the quality of services and facilities be examined. Air conditioners, water heaters, exercise facilities, and conference rooms all require reliable electrical systems. Energy efficiency is essential, especially for facilities that use a lot of power, including heat pump water heaters in restrooms and fitness center equipment. Hotel A in Jakarta Tanah Abang, which has not yet implemented energy conservation measures, requires energy management systems and audits to improve efficiency. The Energy Consumption Intensity (IKE) is the amount of energy used by a building to increase a conditioned area over a month or a year. The study's goal is to determine IKE values for the period February 2024 to June 2024, as well as energy consumption patterns in accordance with the standards. This study included data collecting, interviews, observations, and direct measurements to determine the energy usage of each month and the entire facility. The IKE calculation approach yielded the following findings for each month: February 5,069701417 kWh/m2/month, March 5,235947214 kWh/m2, April 5,009387155 kWh (m2), May 6,335605837 kWh(m2), and June 6,127963403 kWh/m2. With scores ranging from 5 to 6,3 performance energy consumption, electricity falls into the